The Impact Of The Gojek And Tokopedia Mergers On The Welfare Of Gojek Drivers - Suwarsono, Djanut Totok; Basrowi, Basrowi (LPPM Universitas Bina Bangsa, 2021)
Gojek and Tokopedia are now giants in the start-up industry in Indonesia. Tokopedia was the largest E-Commerce in Indonesia for the last few years before the presence of Shopee, which became Tokopedia's main competitor. Meanwhile, Gojek is the largest online transportation company in Indonesia. Combining the two is believed to create a unique ecosystem because it combines e-commerce, on-demand services and financial services in one system. This research aims to find out the welfare impact for Gojek drivers after the Gojek Tokopedia Merger. The method used in this research is qualitative research by interviewing randomly selected informants in Serang Regency, Serang City and Cilegon City. The study was conducted in June 2021, involving ten informants, all of whom were Gojek drivers. This research uses qualitative research methods. The sampling technique used is purposive sampling and snowball sampling. The instrument is the researcher himself as the primary research instrument. The researcher goes directly to the field to meet the informants, conducts interviews now, collects research data, analyzes the data to make conclusions. This study concluded that the Merger between Gojek and Tokopedia, in general, did not affect the welfare of Gojek Drivers, both positive and negative effects